PREPARING FIRST-YEAR ACADEMIC STUDENTS IN UZBEKISTAN FOR THE SAT READING TEST: CHALLENGES, STRATEGIES, AND PEDAGOGICAL IMPLICATIONS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article investigates the challenges and pedagogical strategies involved in preparing first-year academic students in Uzbekistan for the SAT Reading Test, aligning with the national policy on foreign language education and the emphasis on STEM-oriented learning in the 21st century. As Uzbekistan increasingly promotes international education and academic mobility, mastering standardized tests such as the SAT has become vital for students aspiring to pursue higher education abroad. Using a mixed-methods approach, this study explores learners’ difficulties in reading comprehension, inference-making, and academic vocabulary, as well as teachers’ perspectives on integrating SAT reading tasks into English for Academic Purposes (EAP) courses. Findings reveal that contextual adaptation, critical reading instruction, and culturally responsive materials are key to improving performance. The paper argues that bridging English language instruction with SAT-oriented tasks not only supports individual academic success but also advances national educational goals of developing globally competitive, multilingual, and STEM-proficient graduates.